PENGARUH LAMA PERENDAMAN TEMU KUNCI TERHADAP AKTIVITAS PENGHAMBATAN RADIKAL - Puyanda, Irvia Resti; Gibran, Henrikus Andries (JURNAL TEKNOLOGI PERTANIAN, 2024)
Fingerroot is a type of rhizome that is usually added in cooking a dish. The purpose of this study was to determine the effect of soaking time on the total phenolic compounds and radical scavenging activity of the fingerroot soaking time. Fingerroots were washed, chopped, then soaked in distilled water for 0, 10, and 20 minutes at 95°C. Afterwards, screening was carried out followed by testing for radical scavenging activity using the DPPH and ABTS methods, as well as testing for total phenolic compounds. From the results, it was obtained that zero-minute immersion time produced the highest total phenolic compounds and radical scavenging activity (DPPH method), namely 0.70 mg GAE/100g and 6.53%, respectively. Meanwhile, the radical scavenging activity using the ABTS method resulted in the highest value reaching 88.98% for 20 minutes of immersion.